2017
DOI: 10.1002/art.39857
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme A Contributes to Inflammatory Arthritis in Mice Through Stimulation of Osteoclastogenesis

Abstract: GzmA contributes to the joint destruction of RA partly by promoting osteoclast differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…Most studies to date in both mice and humans have shown that Tc17 cells lack cytolytic function (29,31,46,47), although some evidence for cytotoxic function has been reported (24,48). An interesting alternative interpretation of our data is that the secretion of granzymes is not cytolytic but leads to extracellular matrix degradation or promotion of inflammation (49,50). Taken together, these data show that Tc17 cells are armed with an array of proinflammatory mediators, which could act directly on surrounding cells to promote inflammation in the synovial joint.…”
Section: Discussionmentioning
confidence: 71%
“…Most studies to date in both mice and humans have shown that Tc17 cells lack cytolytic function (29,31,46,47), although some evidence for cytotoxic function has been reported (24,48). An interesting alternative interpretation of our data is that the secretion of granzymes is not cytolytic but leads to extracellular matrix degradation or promotion of inflammation (49,50). Taken together, these data show that Tc17 cells are armed with an array of proinflammatory mediators, which could act directly on surrounding cells to promote inflammation in the synovial joint.…”
Section: Discussionmentioning
confidence: 71%
“…The mouse granzyme A inhibitor, Serpinb6b, significantly reduced foot swelling in chikungunya virus–infected mice, indicating that granzyme A may be a potential therapeutic candidate . Granzyme A was also recently shown to be important in a mouse model of rheumatoid arthritis (RA) , an example of the significant overlap between chikungunya arthritis and RA .…”
Section: Chronic Stage Of Chikungunya Virus (>3 Months After the Onsementioning
confidence: 99%
“…In CIA, granzyme A‐deficient mice exhibited reduced joint damage, bone erosion and inflammatory cytokine production compared to wild‐type controls. Interestingly, the authors also demonstrated that granzyme A induces osteoclastogenesis, which may have relevance to its observed function in disease (Santiago et al ., ).…”
Section: Serine Proteinases and Cartilage Ecm Turnovermentioning
confidence: 99%